Integration of Augmented Reality in Chemistry Education to Enhance Students' Science Literacy: A Systematic Literature Review - Putra Yoga Nugraha; Novi Dwi Jayanti; Novita Lestari; Zahrani Sofira Rahman; Muhfidah Lutfia Ulfa; Farah Erika (Jambura Journal of Educational Chemistry, 2026)
Indonesia's persistently low science literacy scores in the 2022 PISA assessment highlight the urgent need for innovative approaches in chemistry education, one of which involves the integration of Augmented Reality (AR). This study aimed to systematically examine the effectiveness of AR integration in chemistry learning in improving students' science literacy through a systematic literature review (SLR) guided by the PRISMA framework. Literature searches were conducted across Scopus and Google Scholar databases using Boolean operator-based keyword combinations, initially retrieving 2,122 articles. Following deduplication, title and abstract screening, and full-text eligibility assessment, 36 articles published between 2021 and 2026 met all inclusion criteria and were included in the final analysis. Findings revealed a significant upward publication trend, particularly in 2024–2025. Research and Development designs predominated (37.8%), with interactive 3D visualization as the most widely applied AR type (32.4%) primarily on Android platforms. Acid-base chemistry, molecular structure, and atomic structure were the most frequently investigated topics. Notably, 83.3% of the reviewed articles reported that AR significantly and positively impacted science literacy and related learning outcomes. Bibliometric analysis using VOSViewer confirmed a substantial research gap between AR, chemistry education, and science literacy. This review affirms that AR represents a promising and accessible technology for improving science literacy in chemistry learning, while identifying opportunities for future studies employing more rigorous experimental designs and standardized measurement instruments.